A cage experiment with four trophic levels: cassava plant growth as influenced by cassava mealybud, Phenacoccus manihoti, its parasitoid Epidinocarsis lopezi,and the hyperparasitoids Prochiloneurus insolitus and Chartocerus hyalipennis - Goergen, Georg E.; Neuenschwander, Peter (1992)
Different combinations of insects belonging to three trophic levels were released in large cages with hydroponie cultures of cassava in a greenhouse. The cassava mealybug (CM )' Phenacoccus manihoti Matile-Ferrero (Horn., Pseudococcidae) was applied at two initial infestation densities to cassava, some of which was grown at different fertilizer levels. Some cages received Epidinocarsis lopezi (De Santis) (Hym., Encyrtidae), the CM specific parasitoid, and/or the hyperparasitoids Prochiloneurus insolitus (Alam) (Hym., Encyrtidae) and Chartocerus hyalipennis Hayat (Hym., Signiphoridae). Plant survival and dry matter production were used to assess the hyperparasitoid's effect via the food chain. All plants infested with CM alone died, while their final dry weight was 34-65 % of the uninfested control. In the presence of E. lopeziy dry matter ranged from 59 to 100 % compared to uninfested plants and depending on the initial CM density. Adding either of the hyperparasitoids did not significantly reduce E. lopezi s efficiency in preventing plant damage. In the presence of both hyperparasitoids and at low initial CM infestation levels, however, dry matter was 58 % of the control, and plant survival was reduced from 93 % to 76%. The generally mild impact of hyperparasitoids in the cage experiments confirms results from the field.